Fermentação etanólica conjunta da batata-doce (Ipomoea batatas (L.) Lam), Mandioca (Manihot esculenta) e Milho (Zea mays) - Silva, Fernanda Aparecida Lima (Universidade Federal do Tocantins, 2017)
How continually see increased demand for energy, especially in the face of rapid population growth and industrial development, it is necessary to increase alternative energy sources. To that end, it has developed a process for producing ethanol using at the same time and in various combinations, sweet potatoe, corn and cassava, optimizing this process is in three trials. The first trial was conducted to evaluate the effect of the concentrations of the enzymes α-amylase (Liquozyme ® SC) and glucoamylase (Spirizyme Fuel ®) in the process of hydrolysis of starch on glucose level. The second trial evaluated the effect of fermentation time and the concentration of the yeast Saccharomyces cerevisiae on the concentration of ethanol. In the last step was explored the fermentation of the three raw materials (industrial sweet potato, cassava and maize) in different combinations, using the best conditions found in the 1st and 2nd tests. The raw sweet potato, cassava and corn had average moisture equal to 66.77%, 66.52% and 13.77%, respectively. The soluble sugar content was 3.41% in sweet potato industry (BDI), 1.73% in cassava (Ma) and 1.65% in corn (Mi). As the starch content, the raw material in nature showed 22.11% and 20.22% for industrial sweet potato and cassava, respectively. Corn kernels, crushed, possessed 41.72%. The test results showed that the optimum range for maximum yield of reducing sugars occurred when 0.36 ml (0.45 g/Kgstarch) of α-amylase (Liquizyme ® SC) and 10.18 ml (11.71 g/Kgstarch) of glucoamylase (Spirizyme Fuel ®) were used per kg of starch (dry basis), and that the optimal condition for fermentation of the mixture (BDI Ma and Mi) was 2.25% yeast and 24 hours of fermentation, in which gave the highest yield of ethanol. When comparing different combinations of raw materials, it was found that the mixture of starch (BDI Ma and Mi), with proportional starch produced the largest amount of ethanol, with an average value of 13,301.62 L/h.